Time‐Dependent Sorption and Desorption of Glyphosate in Soils: Multi‐reaction Modeling - Padilla, J.T. (2020)
Results of batch experiments indicate a high affinity of both soils for GPS, with 24‐h Freundlich coefficients of 158 and 396 Ln mg1−n kg−1 for the Commerce and Sharkey soils, respectively. An apparent time dependency of GPS sorption by both soils was observed, especially within the first 72 h. Changes in solution concentrations of the herbicide beyond 72 h are attributed to both additional sorption as well as solution‐phase degradation. A two‐site multi‐reaction model incorporating time‐dependent reversible and irreversible reactions successfully described the measured data from the batch experiments. However, values of the rate coefficients and sorbed concentrations may be overestimated due to the model's inability to account for degradation processes. Analysis of extracted soil‐bound residues illustrates that degradation of sorbed phase GPS is significant in both soils, although it occurs to a greater extent in the Sharkey soil. Degradation of the herbicide probably occurs through the aminomethylphosphonic acid pathway, as 14C remained associated with the phosphonomethyl group. Models that account for both time‐dependent reactions and degradation will probably lead to improved predictions of the fate of GPS in soils.